2022
DOI: 10.3390/foods11070942
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Auricularia auricula-judae Polysaccharides Alleviate Nutritional Obesity in Mice via Regulating Inflammatory Response and Lipid Metabolism

Abstract: The incidence of lipid metabolism disorder and obesity that is caused by high-calorie diets is increasing year by year, which has become an urgent global health problem. This study was performed to explore the intervention effects of polysaccharides that were extracted from Auricularia auricula-judae resources in the Qinba Mountain area on nutritional obesity in C57BL/6J mice that was induced by high fat and high fructose diets (HFFD) and to investigate their underlying molecular mechanisms. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Polysaccharides from botanical resources have received increasing interest from the world because of their novel structures and diverse bioactivities without harm on the growth of normal cells [6][7][8][9][10][11][12][13]. The bioactivities of polysaccharides are related to their physicochemical properties, including monosaccharide composition, molecular weight, glycosidic bonds, as well as their main-chain and side-chain conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides from botanical resources have received increasing interest from the world because of their novel structures and diverse bioactivities without harm on the growth of normal cells [6][7][8][9][10][11][12][13]. The bioactivities of polysaccharides are related to their physicochemical properties, including monosaccharide composition, molecular weight, glycosidic bonds, as well as their main-chain and side-chain conformations.…”
Section: Introductionmentioning
confidence: 99%
“…When mitochondria produce a large amount of ROS due to excessive oxidation, the nuclear factor kappa-B signaling pathway will be activated, a large amount of lipotoxic substances will be produced, and then inflammatory factors will be activated ( 49 ). Lipotoxicity activates numerous inflammatory factors, such as interleukins (IL-1β and IL-18) and TNF-α ( 50 , 51 ). The occurrence of inflammatory response promotes oxidative stress, thus forming a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides effectively degraded fructan [ 38 ]; and xylan was metabolized by Prevotella bryantii [ 39 ]. In this study, the polysaccharides of Auricularia auricula from the Qinba Mountains prepared by hot water extraction was mainly composed of mannose (the relative molar percentage of mannose, glucuronic acid and xylose is 60.87: 20.83:9.86) [ 4 ], and its regulating effect on intestinal flora may be closely related to mannose. Studies found that mannose is not only an important monosaccharide for protein glycosylation in mammals but also an inefficient source of cell energy.…”
Section: Discussionmentioning
confidence: 99%
“…Then, ethanol was added at a ratio of 1:4 (volume fraction), and alcohol precipitation was carried out for 12 h. The precipitates were separated under 10,000 r/min for 10 min, and fully dissolved in distilled water. After removing protein 4–5 times though the sevage (dichloromethane: n-butanol = 4:1, v / v ) method, cellophane, with a molecular cut-off of 3000 Da, was used for dialysis in flowing tap water for 3 consecutive days, after which the solution was concentrated, freeze-dried, and bagged to obtain the AAP [ 4 ] (the relative mole percentage of mannose, glucuronic acid and xylose was 60.87:20.83:9.86).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation